Trends and challenges in research on integrative health practices and pediatric palliative care: a bibliometric approach - Rocha, Aline Maria de Oliveira; Santos, Flávia H.; Bissoto, João Roberto; Len, Claudio Arnaldo; Iglesias, Simone Brasil de Oliveira (Frontiers in Pediatrics, 2025)
BackgroundApproximately 21 million children and adolescents worldwide require palliative care annually. Pediatric palliative care (PPC) seeks to improve the quality of life of patients, families and caregivers through a holistic and multidisciplinary approach. The integration of palliative care with integrative medicine emphasizes the biopsychosocial well-being of patients by combining pharmacological and non-pharmacological strategies.ObjectivesThis study aims to explore trends and challenges in research on integrative health practices within the context of pediatric palliative care using a bibliometric approach.DesignBibliometric analysis of the scientific literature.MethodsA bibliometric analysis was conducted using relevant databases to identify publications on integrative health practices in pediatric palliative care. Both quantitative and qualitative methods were employed to assess publication trends, key themes and research gaps.ResultsInterest in the integration of palliative care and integrative medicine has grown, highlighting interventions such as therapeutic massage, aromatherapy, hypnosis, meditation/mindfulness and herbal medicine as having therapeutic potential. Nonetheless, communication challenges among patients, families and healthcare professionals remain a barrier to effective implementation.ConclusionIntegrative health practices represent promising, low-cost strategies that can enhance the quality of pediatric palliative care. Future studies should aim to develop effective implementation strategies to broaden access to these practices, thereby reducing suffering and promoting well-being in children and adolescents receiving palliative care.